The Influence of Green Investment and CSR on Firm Value of Banking Sector - Suparti; Lilik Pujiati (Proceeding International Conference on Digital Education and Social Science, 2025)
The primary objective of this study is to empirically investigate how Green Investment and CSR initiatives influence the firm value of the Indonesian banking sector over the 2020–2024 timeframe. This study was prompted by the increasing attention to sustainability issues and the strengthening of regulatory pressure from the Financial Services Authority (OJK) through POJK No. 51/POJK.03/2017. This regulation mandates that financial institutions adopt sustainable financing frameworks. Adopting a quantitative methodology, this research employs multiple linear regression to examine the interplay between variables. Through purposive sampling, 35 banking firms were identified based on predetermined benchmarks. Green Investment is quantified by the proportion of environmental spending relative to total assets, whereas CSR is assessed via the Corporate Social Responsibility Disclosure Index (CSRDI) aligned with GRI standards. The findings indicate that Green Investment significantly and favorably influences firm value, indicating that environmental initiatives increase investor confidence and market perception. Similarly, CSR was found to exert a significant and favorable impact, indicating that broader social responsibility disclosure contributes to increased company value. Overall, this study highlights the strategic importance of sustainability initiatives in strengthening long-term company value and supporting decision-making for management, investors, and regulators.